The structure of a propagating MgAl2O4/MgO interface: linked atomic- and μm-scale mechanisms of interface motion. Issue 23 (12th August 2016) - Li, C.; Griffiths, T.; Pennycook, T. J.; Mangler, C.; Jeřábek, P.; Meyer, J.; Habler, G.; Abart, R.
Abstract: To understand how a new phase forms between two reactant layers, MgAl2 O4 (spinel) has been grown between MgO (periclase) and Al2 O3 (corundum) single crystals under defined temperature and load. Electron backscatter diffraction data show a topotaxial relationship between the MgO reactant and the MgAl2 O4 reaction product. These MgAl2 O4 grains are misoriented from perfect alignment with the MgO substrate by 2–4°, with misorientation axes concentrated in the interface plane. Further study using atomic resolution scanning transmission electron microscopy shows that in 2D the MgAl2 O4 /MgO interface has a periodic configuration consisting of curved segments (convex towards MgO) joined by regularly spaced misfit dislocations occurring every 4.5 nm ( 23 atomic planes). This configuration is observed along the two equivalent [1 0 0] directions parallel to the MgAl2 O4 /MgO interface, indicating that the 3D geometry of the interface is a grid of convex protrusions of MgAl2 O4 into MgO. At each minimum between the protrusions is a misfit dislocation. This geometry results from the coupling between long-range diffusion, which supplies Al 3+ to and removes Mg 2+ from the reaction interface, and interface reaction, in which climb of the misfit dislocations is the rate-limiting process. The extra oxygen atoms required for dislocation climb were likely derived from the reactant MgO, leaving behind oxygen vacancies that eventually form pores at the interface. The pores are dragged along by the propagating reaction interface, providing additional resistance to interface motion. The pinning effect of the pores leads to doming of the interface on the scale of individual grains.